SME Development Through Competitive Advantage on The Improvement of SME Marketing Performance in Medan - Fikri, Muhammad Hilman; Mulyono, Hardi; Syamsuri, Abd. Rasyid; Nainggolan, Solawati (Program Pascasarjana, Universitas Riau, 2024)
The development of competitive advantage for SMEs in Medan City is carried out by looking at the marketing aspects. In improving its marketing performance, SMEs review aspects of market orientation and product innovation. This will allow SMEs to compete with their competitors. The role of the government is also increasingly needed in making the quality improvement of SMEs such as providing facilities and infrastructure for good access to the market, providing understanding in increasing product innovation and opening access to SME marketing in the future. However, some entrepreneurs are constrained in making this because of the limited information and advantages they have. Based on the model and dimensions of the marketing strategy, the results of observational analysis and interviews with speakers conducted by researchers argue that the marketing development strategy of MSMEs in Medan City is included in the progressive strategy model. That is the strategy that is carried out by surviving with the marketing aspect.